Leveraging AI And Blockchain for Secure Digital Right Management in Libraries - Mhsnhasan, Muntader; Selvaraj, Vijayakanthan; Victor, Melvin; Vijayakumar, M.; Kannan, A. S.; Anand, Utkarsh (Indian Journal of Information Sources and Services, 2025)
The urge to develop the Digital rights management systems that are well-established, protecting the intellectual property, and still facilitating the reasonable access to information is supported by the faster rate of digitization of library materials. The given paper investigates how Artificial Intelligence and Blockchain can be combined to support the safety, accountability, and effectiveness of Digital Rights Management (DRM) systems utilized in modern libraries. AI allows advanced content recognition, behavioral analytics, and authorization, the most important features of intelligent and dynamic rights enforcement. Conversely, Blockchain offers an immutable and decentralized historical document into which the administration of licensing agreements, property, and transactions can be documented and which will reduce the chances of illegal access and piracy. Smart contracts are issued in Blockchain platforms that allow libraries to provide license compliance with the administered copyright licensing, real-time auditing control of access, and numerous others. Licensing requirements can be forecasted, irregularities detected, and fair use policies recommended using automated algorithms formulated using content metadata and usage patterns. When these technologies are integrated, it forms a very accurate and trustworthy digital rights management (DRM) system, which is advantageous to the authors, libraries, and users. The study will present a model that has a conceptual framework aimed at showing what AI and Blockchain technology can become in library DRM systems. In the model design, the privacy of the data, data accuracy, and the ability of the system to expand and the legal issues are considered to be major concerns. Besides, the deliberation focuses on the complexity of the constituent parts as well as interoperability and technology ethics. The introduction of other new technologies leads to an unparalleled change in the way digital resources are organized, accessed, and secured in the library setting and introduces increasingly powerful and flexible information systems.